NATIONAL TRADITIONS AS A BASIS FOR TRAINING OF FASHION DESIGNERS - Ніколаєва, Т. В.; Шафранська, Т. В.; Ніколаєва, Т. І. (Art and Design, 2019)
The article includes materials of the research of scientific and methodical bases of training specialists in the field of design and costume design, in order to improve the quality of education of students of the specialty of creative direction, the education of aesthetic taste, national consciousness. In research are used scientific research methods of the literary-analytical, structural and morphological analysis, the method classification of the components of professional competences in the field of education and education the faculties of creative direction, which promote the implementation promising projects of designers of clothing in the country's artistic and cultural space. As a result of research work, it has been established that national culture is the basis of creative activity in various fields of art and design. It is determined that the processes of globalization characteristic of modern society require understanding of the problems of national revival, reflection of the manifestation of the features of national culture in modern design, in particular, the design of clothing. Design methodology becomes an important part of contemporary culture and leads to significant changes in the aesthetic characteristics of the subject environment. The inclusion of the components of national culture and ethno design in the educational design process enables the creation of creative professional design thinking of future designers of clothing. Scientific novelty. It is determined that the generalization of creative principles of design leads to the unification of the characteristics of the subject spatial environment of human existence in the conditions of different national cultures, leveling interesting and rich ethno-artistic traditions. It has been established that national art can be the generator of new ideas in the field of design of clothing. The structure and classification of elements of national and ethno-artistic traditions are revealed. It is expedient to include in the list of competency characteristics of future specialists in the field of design of clothing.